The Quranic Tone of The Wife’s Lament - Zuraikat, Malek J.; Al-Jarrah , Rasheed (Dirasat: Human and Social Sciences, 2024)
Objectives: Relying on the resemblance between the tone and theme of The Wife’s Lament and their counterparts in the Quranic narrative of Virgin Mary’s story, this paper aims at deciphering the devotional tone of The Wife’s Lament, which is an Anglo-Saxon poem that is usually viewed by critics as a woman’s monologue-like confession of her longing and suffering due to her husband’s absence. Methods: The paper reads the poem under discussion by comparing its melancholic diction and atmosphere to the diction and atmosphere of the Quranic narrative of Virgin Mary’s story highlighting the sense of intertextuality between the Anglo-Saxon poem and the Quranic original of the story. Results: Confirming that the woman’s lamentation, in the poem under discussion, is caused by the absence of her male addressee; nevertheless, it shows that identifying such a male addressee is crucial to better understand the poem. We point out that the resemblance between The Wife’s Lament and the Quranic narrative of Virgin Mary’s lamentation caused by her giving birth to a child without being married to a man, implies that the poem’s anonymous addressee in The Wife’s Lament is likely to be God. Conclusion: Against the conventional view that The Wife’s Lament is better read in terms of a wife-husband reproach, this paper concludes that the poem is an allegorical piece that expresses the woman’s fear of wasting much time without contacting God or dedicating herself to medieval monasticism. The poem is a riddle that imitates Mary’s approach of communicating with God, thus promoting it as the ideal means of communication vulnerable Christians should adopt to contact their God without causing themselves any troubles or societal confrontations.